MARKETING STRATEGY TO STRENGTHEN THE COMPETITIVENESS OF SMALL AND MEDIUM INDUSTRIES (IKM) EMPING AFTER THE COVID-19 PANDEMIC - Novi Kadewi Sumbawati; Rosyidah Rachman (Jurnal Ekonomi, 2022)
A change in international policy has from the widespread Covid-19 pandemic, which has affected every country worldwide. Restrictions placed on community activities across all industries, of course, have a significant impact on productivity, particularly for actors involved in business, particularly the Small and Medium Industry (IKM) chips in Sambilawang village, located in the Serang district. The shift in customers' purchasing habits was the cause of the slump in product sales. The development of post-pandemic marketing strategies is an absolute necessity if companies are going to be able to compete effectively. In this research, researchers relied on a qualitative approach that was primarily descriptive. Using SWOT analysis, one can consider internal and external factors and choose the best action. These alternative strategies use SWOT and QSPM metrics to determine marketing strategy priorities. The goal is to make businesses more competitive after the pandemic has passed. The objective of the research was to devise a post-pandemic marketing strategy to increase the competitiveness of emping SMEs doing business in Sambilawang Village, located in the Serang Regency. The study's findings should aid SMEs in expanding the distribution of emping products in Sambilawang, a village in Indonesia. The results revealed that the Sambilawang village's Small and Medium Emping Industries located in quadrant V, with an IFAS value of 2.7042, an EFAS value of 2.9441, and an alternative strategy based on the priority of the QSPM matrix value of 4.9626, namely increasing product promotion through digital marketing and digital branding. To broaden the marketing network through the market and collaboration with relevant agencies and local governments, to enhance one's skill set, expand one's access to business capital, and secure additional patents.